Mastering geospatial analysis with Python : explore GIS processing and learn to work with GeoDjango, CARTOframes and MapboxGL-Jupyter /: explore GIS processing and learn to work with GeoDjango, CARTOframes and MapboxGL-Jupyter. (2018) - Crickard, Paul; Toms, Silas; Rees, Eric van
No abstract available